Pengembangan Media Video Tutorial Pembuatan Saku Passepoille Mata Pelajaran Menjahit Produk Busana Di Kelas XI SMK Negeri 3 Blitar - Ilma Ainu Sofa (Jurnal Bintang Pendidikan Indonesia, 2024)
The aims of this research are (1) to determine the feasibility of developing video tutorials (2) to determine students’ responses to the use of video tutorial media for making passinelle pockets for clothing sewing subjects as a learning medium. This type of research is Research and Development (R&D). This research was carried out at SMK Negeri 3 Blitar which is located at Jl. S. Supriadi No. 24C, Bendogerit, District. Sananwetan, Blitar City in class XI Fashion Design with a total of 35 students. The data collection method used was the interview method, namely to determine the development of the video tutorial media for making passinelle pockets in the subject of sewing fashion products in class XI clothing 2, as well as the response questionnaire method to determine students’ responses to the use of video tutorial media as a learning medium. The results of this research stated that the development of video tutorial media was seen from the validity test by material experts at 87% and the validity by media experts obtained a figure of 86.5% so that the average data obtained was 86.5% and was declared very feasible. Students’ responses to the use of video tutorial media obtained an average percentage of 90.5% and were included in the very good category.